Results of experimental modeling of postoperative peritoneal adhesions - M. H. Melnychenko; V. O. Sytnikova; A. A. Kvashnina (Zaporozhye State Medical University, 2019)
Objective: Optimization of postoperative intraabdominal adhesions modeling. Material and methods. The objects of the study were 17 mature rats of the Wistar line of both sexes weighing 200-250 g. Experimental modeling of postoperative intraabdominal adhesions was carried out under aseptic conditions (the 1st series, 11 animals) and in peritonitis conditions (the 2nd series, 6 animals) . Results. We have used the Matoba score scale for the quantitative assessment of the adhesion process, as well as to analyze the models with the involvement of the cecum: the average score of the adhesion process in the 1st group was 4.90 (3.00; 6.00), in the peritonitis conditions - 4.83 (2.00; 7.00). Formation of the intraperitoneal adhesion process was achieved in all experimental animals (100 %). Formation of adhesions between the cecum and the abdominal wall was noted in 66.7 % of cases. Conclusions. For the experimental reproduction of intraabdominal adhesions in aseptic conditions, it is advisable to use a method of simulation by abrasions of the serous cover of cecum with a cervical brush along the intestine till the appearance of spot hemorrhages in the form of "blood dew" and damage to the parietal peritoneum in the lower quadrants, which provides the development of adhesive intraabdominal process in all experimental animals. For experimental reproduction of intraabdominal adhesions in peritonitis it is expedient for 20 hours prior to the above-described method of modeling to complete an intraperitoneal injection of 2 ml of fecal suspension into a physiological solution of sodium chloride, which provides the development of an adhesive intra-abdominal process under conditions of fibrinous purulent peritonitis in all experimental animals. The obtained data allowed to consider the developed models to be adequate for further experimental research with the aim of studying intraabdominal prophylaxis of adhesion formation under conditions of infection and in aseptic conditions.